Acute Effects of Whole Body Vibration Training on Agility in Sedentary Men - Aksoy, Duygu (Progress in Nutrition, 2021)
Study Objectives: The aim of the study was to investigate the effects of Acute Whole Body Vibration Training on agility in sedentary men. Methods: Twenty healthy sedentary male volunteers who were aged between 18 and 25 participated in the study. Participants were divided into two groups as Acute Whole Body Vibration Training and Control Group. The agility performance values ​​of the participants were determined with the Agility T-Test. Results were given in mean ± standard deviation. Independent samples t test was used to compare among independent examples. Paired sample t test was used to compare among the dependent examples. The significance level was taken as p<0.05. Results: Based on the results, it was found that there was no positive development between the pretest and posttest values ​​of the Acute Whole Body Vibration Training Group. No statistically significant differences were detected in this respect (p>0.05). It was also found that there was no improvement between the pretest and posttest values ​​of the control group. No statistically significant differences were detected in this respect (p>0.05). There were no statistically significant differences between the pre-test and post-test values ​​of the groups. Conclusion: It can be argued that Acute Whole Body Vibration Training does not increase agility performance in sedentary men.